PERBANDINGAN PENGUKURAN STATUS SEDASI RICHMOND AGITATION SEDATION SCALE (RASS) DAN RAMSAY SEDATION SCALE (RSS) PADA PASIEN GAGAL NAFAS TERHADAP LAMA WEANING VENTILATOR DI GICU RSUP Dr.HASAN SADIKIN BANDUNG - Hellena Deli; Muhammad Zafrullah Arifin; Sari Fatimah (Jurnal Riset Kesehatan, 2017)
Sedation is an important factor to improve patient comfort. Over sedation may lead to a longer ventilator time. To prevent over sedation need an instrument can measure accurately the status of sedation. This study aimed to analyze the differences between Richmond Agitation Sedation Scale (RASS) and the Ramsay Sedation Scale (RSS) in measuring the status of sedation for respiratory failure patient against time weaning ventilator. This study is observational analytic with prospective cohort study. This study was conducted in 13 respiratory failure patient and use mechanical ventilator. Sampling is done by non probability sampling method with consecutive sampling that received sedation therapy in GICU RSUP Dr Hasan Sadikin, Bandung. Samples will be measured with two sedation instrument they are RASS and RSS. Patient will be observed until the patient is successfully weaning ventilator mode CPAP or CPAP PS with PS 5-8 cmH2O and PEEP 5 cmH2O.These results indicate the measurement status with RASS sedation and RSS have a significant impact on weaning ventilator time with a value of p less than 0.05. Based on analysis results there is a significant difference between the measurement of sedation status by RASS and RSS for respiratory failure patient and weaning ventilator time with p less than 0.05, and the post hoc analysis shows that there are differences in each measurement sedation with p less than 0,05.Measurement status with RASS sedation better in reducing the length of ventilator weaning compared to RSS. This study can be used as the basis for further research regarding the relationship status measurement sedation to morbidity, mortality and length of stay in patients receiving sedation therapy.